Fireproof rubber foamed sponge and preparation method thereof
By adding nano-silica, silane coupling agent, antibacterial agent and antistatic agent to the fire-resistant rubber foam sponge, and using specific preparation methods, the traditional fire-resistant rubber foam sponge is easily combustible and mechanically strong under high-temperature flames. Insufficient and prone to bacterial and static problems have significantly improved the fire resistance, mechanical strength, antibacterial properties and antistatic properties of the material.
Patent Information
- Application Number
- CN202411673429.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-14
AI Technical Summary
Traditional fire-resistant rubber foam sponges are prone to flammability under high temperature flames, lack of mechanical strength, prone to bacterial growth, and have serious static problems, affecting their application safety and service life.
By adding nanosilica, silane coupling agent, antibacterial agent and antistatic agent, and using aerosol-assisted assembly technology and cold plasma treatment methods, we can prepare enhanced fire resistance, mechanical strength, antibacterial properties and antistatic properties with antistatic properties with enhanced fire resistance, mechanical strength, antibacterial properties and antistatic properties by using aerosol-assisted assembly technology and cold plasma treatment methods. Performance fire-resistant rubber foam sponge.
It significantly improves the fire resistance, mechanical strength, antibacterial properties and antistatic properties of the sponge, solves the problems of flammable, insufficient mechanical strength, and easy breeding of bacteria and static electricity under high temperature flames, and improves the safety and service life of the material. And reduce production costs and energy consumption.
Smart Images

Figure CN119432050A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, in particular to a fireproof rubber foam sponge and a preparation method thereof. Background Art
[0002] In modern construction, transportation and electronics, fire-resistant rubber foam sponge is a key material that is widely used due to its excellent fire resistance, heat preservation, sound insulation and shock absorption properties. For example, in the construction industry, fire-resistant rubber foam sponge is often used as a fireproof insulation layer for walls and ceilings to ensure that the building can effectively prevent the spread of fire in the event of a fire; in the transportation field, this material is used as a fireproof filler for vehicle and aircraft interiors to improve overall safety; in the electronics field, fire-resistant rubber foam sponge is used for insulation and protection of electronic equipment to prevent damage caused by fire.
[0003] Although the application of fire-resistant rubber foam sponge in the above-mentioned fields has brought significant safety benefits, with the development of technology and the continuous increase in application demand, traditional fire-resistant rubber foam sponge has gradually exposed some problems in actual use. First of all, although traditional fire-resistant rubber foam sponge can provide fire protection to a certain extent, it is still easy to burn under high-temperature flames and may produce dripping. This not only reduces the fire resistance of the material, but may also aggravate the spread of fire and increase the harm of fire.
[0004] In addition, the lack of mechanical strength is also an important problem faced by traditional fire-resistant rubber foam sponges. In practical applications, this material is often prone to breakage and deformation, especially in situations where high strength and high durability are required. This limitation in mechanical properties restricts the use of fire-resistant rubber foam sponges in certain key applications, affecting their overall performance and service life.
[0005] In an environment with high humidity, traditional fireproof rubber foam sponges are also prone to breeding bacteria, causing the material to mold and deteriorate. This not only affects its physical properties, but may also pose health risks, especially in places where long-term contact is required, such as public buildings and transportation interiors. In addition, static electricity is also a major problem in the application of traditional fireproof rubber foam sponges in the electronics and electrical fields. The material is prone to generate static electricity during use, which may damage electronic components and affect the normal operation of the equipment.
[0006] In order to meet these challenges, the present invention provides a fire-resistant rubber foam sponge and a preparation method thereof. Summary of the invention
[0007] In view of the deficiencies in the prior art, the present invention provides a fireproof rubber foam sponge and a preparation method thereof, which solves the problems of the traditional fireproof rubber foam sponge in terms of fireproof performance, mechanical strength, antibacterial performance, antistatic performance and production efficiency.
[0008] To achieve the above objectives, the present invention is implemented through the following technical scheme: the fireproof rubber foam sponge includes the following components by weight percentage: 50%-60% of polyether polyol, 30%-40% of isocyanate, 2%-5% of water, 0.3%-1% of catalyst, 0.5%-2% of foam stabilizer, 5%-10% of flame retardant, 3%-6% of nano silicon dioxide, 8%-15% of bio-based polyol, 0.5%-2% of antibacterial agent, 1%-3% of antistatic agent and 1%-3% of silane coupling agent.
[0009] Preferably, the catalyst is optionally selected from one of an organic tin compound, a tertiary amine catalyst or an organometallic compound, and the foam stabilizer is optionally selected from one of a siloxane stabilizer, a polyether stabilizer or an organosilicon polyether copolymer.
[0010] Preferably, the flame retardant is selected from one of halogen flame retardants, phosphorus flame retardants or nitrogen flame retardants, and the antibacterial agent is selected from one of silver nanoparticles, copper nanoparticles or triclosan.
[0011] Preferably, the antistatic agent is optionally one of alkyl dimethyl benzyl ammonium chloride, tributyl phosphate or acetylene black, and the silane coupling agent is optionally one of γ-aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane or vinyl trimethoxysilane.
[0012] The method for preparing a fireproof rubber foam sponge comprises the following steps:
[0013] S1, mixing nano-silica with a silane coupling agent and treating it by aerosol-assisted assembly technology;
[0014] S2, dissolving polyether polyol, bio-based polyol and water in a suitable solvent, and stirring with a magnetic stirrer for 25-30 minutes;
[0015] S3, add foam stabilizer, catalyst and pretreated nano-silicon dioxide solution, and continue stirring for 10-15 minutes;
[0016] S4, subjecting the uniformly mixed polyol mixture and isocyanate to cold plasma treatment in a low temperature environment;
[0017] S5, first curing at room temperature;
[0018] S6, performing secondary curing;
[0019] S7, impregnating the solidified sponge with an antibacterial agent and an antistatic agent;
[0020] S8. Drying is performed in a vacuum dryer.
[0021] Preferably, the aerosol-assisted assembly technology process in step S1 specifically includes the following steps:
[0022] Solution atomization: Use an ultrasonic atomizer to atomize the uniformly dispersed nano-solution into tiny droplets. The frequency of the ultrasonic atomizer is set between 1.7MHz-2.4MHz to produce droplets with a diameter of about 1-10 microns;
[0023] Aerosol formation: The atomized droplets are transported to the aerosol reactor through the carrier gas to form a stable aerosol;
[0024] Aerosol reaction: In the aerosol reactor, the electric field and airflow are used to control the dispersion and deposition of droplets. The electric field strength is set at 0.5-2kV / cm, and the airflow velocity is set at 0.1-1m / s. The nanomaterials are evenly dispersed and covered on the substrate or other target surface in the reactor;
[0025] Deposition and drying: At room temperature, the aerosol passing through the aerosol reactor is uniformly deposited under the action of the electric field and airflow. The deposition time is 10-30 minutes to form a uniform nano-coating. The deposited material is dried at 60℃-80℃ for 30-60 minutes, leaving uniformly distributed nanoparticles.
[0026] Preferably, the carrier gas is nitrogen or air, and its flow rate is set at 1-5 L / min.
[0027] Preferably, the appropriate solvent in step S2 is alcohol or acetone, the curing time in step S5 is 1-3 hours, the curing temperature in step S6 is 70-90° C., and the secondary curing time is 1-4 hours.
[0028] Preferably, the immersion treatment in step S7 specifically includes the following steps:
[0029] The solidified sponge is completely immersed in the comprehensive functional solution, and the surface and the inside of the sponge are fully in contact with the solution;
[0030] In an environment of 20℃-30℃, gently stir or shake the solution and soak for 20-40 minutes;
[0031] Remove the sponge: Once the dipping is complete, remove the sponge from the solution and gently squeeze to remove any excess solution.
[0032] The comprehensive functional solution is formed by mixing an antibacterial agent solution and an antistatic agent solution in a ratio of 1:1.
[0033] The present invention provides a fireproof rubber foam sponge and a preparation method thereof. It has the following beneficial effects:
[0034] 1. The present invention greatly improves the fireproof performance of the sponge by adding materials such as nano-silicon dioxide and silane coupling agent and improving the preparation method, which is manifested in that the burning time is significantly shortened and there is no dripping phenomenon, thereby solving the defects of traditional fire-resistant rubber foam sponge that is easy to burn under flames and may drip, and improving the fire safety of the material.
[0035] 2. The present invention significantly improves the mechanical strength and elongation at break of the sponge by adding materials such as nano-silicon dioxide and silane coupling agent, solves the problem of insufficient mechanical strength and easy breakage of traditional fire-resistant rubber foam sponge, and makes the material more durable and reliable in application.
[0036] 3. The present invention adds antibacterial agents such as silver nanoparticles to make the sponge have significant antibacterial properties, with a colony reduction rate of up to 95%, solving the problem that traditional fire-resistant rubber foam sponges are prone to breeding bacteria in humid environments and improving the hygiene and safety of the material.
[0037] 4. The present invention significantly reduces the surface resistance of the sponge and enhances the antistatic performance by adding antistatic agents such as alkyl dimethyl benzyl ammonium chloride, thereby solving the problem that traditional fireproof rubber foam sponges are prone to generate static electricity during use and improving the safety and applicability of the material in the fields of electronics and electrical appliances.
[0038] 5. The present invention adopts aerosol-assisted assembly technology and cold plasma treatment method, which significantly shortens the preparation time of sponge and reduces energy consumption, solves the problems of long time and high energy consumption of traditional preparation methods, improves production efficiency and reduces production costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 It is a flow chart of the present invention. DETAILED DESCRIPTION
[0040] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] Please refer to the attached Figure 1 The embodiment of the present invention provides a fireproof rubber foam sponge, which includes the following components by weight percentage: 50%-60% polyether polyol, 30%-40% isocyanate, 2%-5% water, 0.3%-1% catalyst, 0.5%-2% foam stabilizer, 5%-10% flame retardant, 3%-6% nano silicon dioxide, 8%-15% bio-based polyol, 0.5%-2% antibacterial agent, 1%-3% antistatic agent, and 1%-3% silane coupling agent.
[0042] The catalyst is optionally selected from one of an organic tin compound, a tertiary amine catalyst or an organic metal compound, and the foam stabilizer is optionally selected from one of a siloxane stabilizer, a polyether stabilizer or an organic silicon polyether copolymer.
[0043] The flame retardant is optionally selected from one of halogen flame retardants, phosphorus flame retardants or nitrogen flame retardants, and the antibacterial agent is optionally selected from one of silver nanoparticles, copper nanoparticles or triclosan.
[0044] The antistatic agent is optionally selected from alkyl dimethyl benzyl ammonium chloride, tributyl phosphate or acetylene black, and the silane coupling agent is optionally selected from γ-aminopropyl triethoxysilane, γ-glycidyl ether oxypropyl trimethoxysilane or vinyl trimethoxysilane.
[0045] A method for preparing a fireproof rubber foam sponge, characterized in that the method is prepared by using the fireproof rubber foam sponge component material according to any one of claims 1 to 4, and comprises the following steps:
[0046] S1, mixing nano-silica with a silane coupling agent and treating it by aerosol-assisted assembly technology;
[0047] S2, dissolving polyether polyol, bio-based polyol and water in a suitable solvent, and stirring with a magnetic stirrer for 25-30 minutes;
[0048] S3, add foam stabilizer, catalyst and pretreated nano-silicon dioxide solution, and continue stirring for 10-15 minutes;
[0049] S4, subjecting the uniformly mixed polyol mixture and isocyanate to cold plasma treatment in a low temperature environment;
[0050] S5, first curing at room temperature;
[0051] S6, performing secondary curing;
[0052] S7, impregnating the solidified sponge with an antibacterial agent and an antistatic agent;
[0053] S8. Drying is performed in a vacuum dryer.
[0054] The aerosol-assisted assembly technology process in step S1 specifically includes the following steps:
[0055] Solution atomization: Use an ultrasonic atomizer to atomize the uniformly dispersed nano-solution into tiny droplets. The frequency of the ultrasonic atomizer is set between 1.7MHz-2.4MHz to produce droplets with a diameter of about 1-10 microns;
[0056] Aerosol formation: The atomized droplets are transported to the aerosol reactor through the carrier gas to form a stable aerosol;
[0057] Aerosol reaction: In the aerosol reactor, the electric field and airflow are used to control the dispersion and deposition of droplets. The electric field strength is set at 0.5-2kV / cm, and the airflow velocity is set at 0.1-1m / s. The nanomaterials are evenly dispersed and covered on the substrate or other target surface in the reactor;
[0058] Deposition and drying: At room temperature, the aerosol passing through the aerosol reactor is uniformly deposited under the action of the electric field and airflow. The deposition time is 10-30 minutes to form a uniform nano-coating. The deposited material is dried at 60℃-80℃ for 30-60 minutes, leaving uniformly distributed nanoparticles.
[0059] The carrier gas is nitrogen or air, and its flow rate is set at 1-5 L / min.
[0060] The appropriate solvent in step S2 is alcohol or acetone, the curing time in step S5 is 1-3 hours, the curing temperature in step S6 is 70-90° C., and the secondary curing time is 1-4 hours.
[0061] The comprehensive functional solution is formed by mixing an antibacterial agent solution and an antistatic agent solution in a ratio of 1:1.
[0062] Embodiment 1:
[0063] Formula ingredients (weight percentage):
[0064] Polyether polyol: 50%
[0065] Isocyanate: 30%
[0066] Water: 3%
[0067] Catalyst: 0.5%
[0068] Foam stabilizer: 1%
[0069] Flame retardant: 6%
[0070] Nano silicon dioxide: 5%
[0071] Bio-based polyols: 10%
[0072] Antimicrobial: 1%
[0073] Antistatic agent: 2%
[0074] Silane coupling agent: 1.5%
[0075] Preparation method steps:
[0076] Nanomaterial pretreatment:
[0077] Weigh 5% of nano-silica and 1.5% of silane coupling agent.
[0078] Nano-silica and silane coupling agent were mixed in ethanol and stirred at 27° C. for 30 minutes.
[0079] The mixed solution was atomized into droplets with a diameter of 1-10 μm using an ultrasonic atomizer (frequency 2 MHz).
[0080] The atomized droplets were transported to the aerosol reactor by a carrier gas (nitrogen, flow rate 3 L / min), with an electric field strength of 1 kV / cm and a gas flow velocity of 0.5 m / s.
[0081] Deposition was carried out at room temperature for 20 min and then dried at 70 °C for 40 min.
[0082] Polyol mixture preparation:
[0083] 50% of polyether polyol, 10% of bio-based polyol and 3% of water were dissolved in ethanol and stirred for 27 minutes.
[0084] Add 1% of foam stabilizer and 0.5% of catalyst, then add the pretreated nano-silicon dioxide solution, and continue stirring for 12 minutes.
[0085] Foaming process:
[0086] The uniformly mixed polyol mixture and 30% isocyanate were subjected to cold plasma treatment in a -40°C environment for 5 minutes.
[0087] First cure:
[0088] The primary curing was carried out at 22°C for 2 hours.
[0089] Secondary curing:
[0090] Post-curing was carried out at 80°C for 3 hours.
[0091] Dipping treatment:
[0092] The cured sponge was immersed in a 1% silver nanoparticle solution and a 2% alkyl dimethyl benzyl ammonium chloride solution (mixed in a ratio of 1:1) and immersed in an environment of 25° C. for 30 minutes with slight stirring.
[0093] Remove the sponge and squeeze gently to remove any excess solution.
[0094] Vacuum drying:
[0095] Dry in a vacuum desiccator at 40°C for 3 hours.
[0096] Summary of Example 1:
[0097] This example prepares a fire-resistant rubber foam sponge using a basic formula and standard processing techniques to ensure its basic functionality and structural integrity.
[0098] Embodiment 2:
[0099] Formula ingredients (weight percentage):
[0100] Polyether polyol: 52%
[0101] Isocyanate: 32%
[0102] Water: 4%
[0103] Catalyst: 0.7%
[0104] Foam stabilizer: 1.2%
[0105] Flame retardant: 7%
[0106] Nano silicon dioxide: 4%
[0107] Bio-based polyols: 8%
[0108] Antimicrobial: 0.8%
[0109] Antistatic agent: 1.5%
[0110] Silane coupling agent: 2%
[0111] Preparation method steps:
[0112] Nanomaterial pretreatment:
[0113] Weigh 4% of nano-silica and 2% of silane coupling agent.
[0114] Nano-silica and silane coupling agent were mixed in ethanol and stirred at 28° C. for 30 minutes.
[0115] The mixed solution was atomized into droplets with a diameter of 1-10 μm using an ultrasonic nebulizer (frequency 2.1 MHz).
[0116] The atomized droplets were transported to the aerosol reactor by a carrier gas (air, flow rate 4 L / min), with an electric field strength of 1.2 kV / cm and an air flow velocity of 0.8 m / s.
[0117] Deposition was carried out at room temperature for 25 minutes and then dried at 75 °C for 45 minutes.
[0118] Polyol mixture preparation:
[0119] 52% of polyether polyol, 8% of bio-based polyol and 4% of water were dissolved in acetone and stirred for 28 minutes.
[0120] 1.2% of foam stabilizer and 0.7% of catalyst were added, and then the pretreated nano-silicon dioxide solution was added, and stirring was continued for 13 minutes.
[0121] Foaming process:
[0122] The uniformly mixed polyol mixture and 32% isocyanate were subjected to cold plasma treatment in a -35°C environment for 6 minutes.
[0123] First cure:
[0124] The primary curing was carried out at 23°C for 2.5 hours.
[0125] Secondary curing:
[0126] Post-curing was carried out at 82°C for 3.5 hours.
[0127] Dipping treatment:
[0128] The cured sponge was immersed in 0.8% copper nanoparticle solution and 1.5% tributyl phosphate solution (1:1 mixture) and immersed in an environment of 26° C. for 35 minutes with slight stirring.
[0129] Remove the sponge and squeeze gently to remove any excess solution.
[0130] Vacuum drying:
[0131] Dry in a vacuum desiccator at 42°C for 3.5 hours.
[0132] Example 2 Summary:
[0133] The formulation ratio and operating parameters were adjusted on the basis of Example 1 to further optimize the fire resistance and mechanical strength of the sponge.
[0134] Embodiment 3:
[0135] Formula ingredients (weight percentage):
[0136] Polyether polyol: 54%
[0137] Isocyanate: 34%
[0138] Water: 3.5%
[0139] Catalyst: 0.6%
[0140] Foam stabilizer: 1.5%
[0141] Flame retardant: 6.5%
[0142] Nano silicon dioxide: 3.5%
[0143] Bio-based polyols: 10%
[0144] Antimicrobial: 1.5%
[0145] Antistatic agent: 2.5%
[0146] Silane coupling agent: 1.8%
[0147] Preparation method steps:
[0148] Nanomaterial pretreatment:
[0149] Weigh 3.5% of nano-silicon dioxide and 1.8% of silane coupling agent.
[0150] Nano-silica and silane coupling agent were mixed in ethanol and stirred at 27° C. for 30 minutes.
[0151] The mixed solution was atomized into droplets with a diameter of 1-10 μm using an ultrasonic nebulizer (frequency 2.3 MHz).
[0152] The atomized droplets were transported to the aerosol reactor by a carrier gas (nitrogen, flow rate 4.5 L / min), with an electric field strength of 1.5 kV / cm and a gas flow velocity of 0.6 m / s.
[0153] Deposition was carried out at room temperature for 20 min and then dried at 70 °C for 50 min.
[0154] Polyol mixture preparation:
[0155] 54% of polyether polyol, 10% of bio-based polyol and 3.5% of water were dissolved in acetone and stirred for 28 minutes.
[0156] 1.5% of foam stabilizer and 0.6% of catalyst were added, and then the pretreated nano-silicon dioxide solution was added, and stirring was continued for 12 minutes.
[0157] Foaming process:
[0158] The uniformly mixed polyol mixture and 34% isocyanate were subjected to cold plasma treatment in a -38°C environment for 5 minutes.
[0159] First cure:
[0160] Primary curing was carried out at 24°C for 2 hours.
[0161] Secondary curing:
[0162] Secondary curing was carried out at 80°C for 3 hours.
[0163] Dipping treatment:
[0164] The cured sponge was immersed in 1.5% silver nanoparticle solution and 2.5% alkyl dimethyl benzyl ammonium chloride solution (mixed in a ratio of 1:1) and immersed in an environment of 27° C. for 30 minutes with slight stirring.
[0165] Remove the sponge and squeeze gently to remove any excess solution.
[0166] Vacuum drying:
[0167] Dry in a vacuum desiccator at 45°C for 4 hours.
[0168] Example 3 Summary:
[0169] By adjusting the material ratio and process parameters, this embodiment further enhances the antibacterial and antistatic properties of the sponge.
[0170] Embodiment 4:
[0171] Formula ingredients (weight percentage):
[0172] Polyether polyol: 56%
[0173] Isocyanate: 35%
[0174] Water: 4%
[0175] Catalyst: 0.8%
[0176] Foam stabilizer: 1.8%
[0177] Flame retardant: 7%
[0178] Nano silicon dioxide: 4%
[0179] Bio-based polyols: 8%
[0180] Antimicrobial: 1.8%
[0181] Antistatic agent: 2%
[0182] Silane coupling agent: 1.5%
[0183] Preparation method steps:
[0184] Nanomaterial pretreatment:
[0185] Weigh 4% of nano-silicon dioxide and 1.5% of silane coupling agent.
[0186] Nano-silica and silane coupling agent were mixed in ethanol and stirred at 28° C. for 30 minutes.
[0187] The mixed solution was atomized into droplets with a diameter of 1-10 μm using an ultrasonic atomizer (frequency 2.2 MHz).
[0188] The atomized droplets were transported to the aerosol reactor by a carrier gas (air, flow rate 3.5 L / min), with an electric field strength of 1.4 kV / cm and an air flow velocity of 0.7 m / s.
[0189] Deposition was carried out at room temperature for 30 min and then dried at 80 °C for 45 min.
[0190] Polyol mixture preparation:
[0191] 56% of polyether polyol, 8% of bio-based polyol and 4% of water were dissolved in acetone and stirred for 30 minutes.
[0192] 1.8% of foam stabilizer and 0.8% of catalyst were added, and then the pretreated nano-silicon dioxide solution was added, and stirring was continued for 15 minutes.
[0193] Foaming process:
[0194] The uniformly mixed polyol mixture and 35% isocyanate were subjected to cold plasma treatment in a -30°C environment for 8 minutes.
[0195] First cure:
[0196] The primary curing was carried out at 25°C for 2.5 hours.
[0197] Secondary curing:
[0198] Post-curing was carried out at 85°C for 3 hours.
[0199] Dipping treatment:
[0200] The cured sponge was immersed in 1.8% copper nanoparticle solution and 2% tributyl phosphate solution (1:1 mixture) and immersed in an environment of 25° C. for 40 minutes with slight stirring.
[0201] Remove the sponge and squeeze gently to remove any excess solution.
[0202] Vacuum drying:
[0203] Dry in a vacuum desiccator at 50°C for 3.5 hours.
[0204] Example 4 Summary:
[0205] Based on the above-mentioned embodiments, this embodiment further optimizes the foaming and impregnation treatment processes, thereby improving the durability and stability of the sponge.
[0206] Embodiment 5:
[0207] Formula ingredients (weight percentage):
[0208] Polyether polyol: 60%
[0209] Isocyanate: 40%
[0210] Water: 5%
[0211] Catalyst: 1%
[0212] Foam stabilizer: 2%
[0213] Flame retardant: 10%
[0214] Nano silicon dioxide: 6%
[0215] Bio-based polyols: 12%
[0216] Antimicrobial: 2%
[0217] Antistatic agent: 3%
[0218] Silane coupling agent: 3%
[0219] Preparation method steps:
[0220] Nanomaterial pretreatment:
[0221] Weigh 6% of nano-silicon dioxide and 3% of silane coupling agent.
[0222] Nano-silica and silane coupling agent were mixed in ethanol and stirred at 29° C. for 30 minutes.
[0223] The mixed solution was atomized into droplets with a diameter of 1-10 μm using an ultrasonic atomizer (frequency 2.4 MHz).
[0224] The atomized droplets were transported to the aerosol reactor by a carrier gas (nitrogen, flow rate 4.5 L / min), with an electric field strength of 2 kV / cm and a gas flow velocity of 0.9 m / s.
[0225] Deposition was carried out at room temperature for 30 min and then dried at 80 °C for 60 min.
[0226] Polyol mixture preparation:
[0227] 60% of polyether polyol, 12% of bio-based polyol and 5% of water were dissolved in acetone and stirred for 30 minutes.
[0228] Add 2% of foam stabilizer and 1% of catalyst, then add the pretreated nano-silicon dioxide solution and continue stirring for 15 minutes.
[0229] Foaming process:
[0230] The uniformly mixed polyol mixture and 40% isocyanate were subjected to cold plasma treatment in a -20°C environment for 10 minutes.
[0231] First cure:
[0232] The preliminary curing was carried out at 25°C for 3 hours.
[0233] Secondary curing:
[0234] Secondary curing was carried out at 90°C for 4 hours.
[0235] Dipping treatment:
[0236] The cured sponge was immersed in a 2% triclosan solution and a 3% acetylene black solution (mixed in a ratio of 1:1), and the mixture was gently stirred and immersed in an environment of 30° C. for 40 minutes.
[0237] Remove the sponge and squeeze gently to remove any excess solution.
[0238] Vacuum drying:
[0239] Dry in a vacuum desiccator at 50°C for 4 hours.
[0240] Summary of Example 5:
[0241] Based on the above-mentioned embodiments, this embodiment significantly improves the comprehensive performance of the fire-resistant rubber foam sponge by further increasing the concentration of the ingredients and optimizing the processing technology.
[0242] Summary:
[0243] Example 1: Basic formulation and standard processing techniques to ensure basic functionality and structural integrity.
[0244] Example 2: Adjust the formulation ratio and operating parameters to further optimize the fire resistance and mechanical strength.
[0245] Example 3: Adjusting material proportions and process parameters to enhance antibacterial and antistatic properties.
[0246] Example 4: Optimizing the foaming and impregnation processes to improve durability and stability.
[0247] Example 5: Increasing ingredient concentration and optimizing processing technology can significantly improve overall performance.
[0248] Experiment 1: Study the effects of different additives on the performance of fire-resistant rubber foam sponge
[0249] Purpose:
[0250] Explore the effects of different additives on the performance of fire-resistant rubber foam sponge, and screen out materials that can significantly improve the performance of the sponge.
[0251] Experimental design:
[0252] Sample preparation:
[0253] Sample 1: Traditional fire-resistant rubber foam sponge (control group)
[0254] Sample 2: Sponge with added nano-silica (5%)
[0255] Sample 3: Sponge with added graphene (5%)
[0256] Sample 4: Sponge with added carbon nanotubes (5%)
[0257] Sample 5: Sponge with silane coupling agent (2%) added
[0258] Sample 6: Sponge with added antimicrobial agent (silver nanoparticles, 1%)
[0259] Sample 7: Sponge with antistatic agent (alkyl dimethyl benzyl ammonium chloride, 1%) added
[0260] Performance Testing:
[0261] Fire resistance (UL-94 horizontal and vertical burning test)
[0262] Mechanical strength (tensile test)
[0263] Antibacterial properties (quantitative contact bactericidal test)
[0264] Antistatic performance (surface resistance test)
[0265] Experimental steps:
[0266] Sample preparation:
[0267] According to the characteristics of each material, add it into the preparation process of fire-resistant rubber foam sponge in proportion, and prepare the sample according to the following steps:
[0268] Polyether polyol, bio-based polyol and water were dissolved in appropriate solvents and stirred using a magnetic stirrer for 30 minutes.
[0269] Add the foam stabilizer, catalyst and pre-treated additives and continue stirring for 15 minutes.
[0270] The uniformly mixed polyol mixture and isocyanate are subjected to cold plasma treatment in a low temperature environment.
[0271] The primary curing was carried out at room temperature for 1 hour, and the secondary curing was carried out at 80°C for 2 hours.
[0272] The solidified sponge is dried.
[0273] Performance Testing:
[0274] Fire performance test: The sample is cut into a size of 100mm×10mm×3mm and subjected to the UL-94 horizontal and vertical burning test, and the burning time and whether there is dripping are recorded.
[0275] Mechanical strength test: The samples were cut into a standard dumbbell shape (ASTM D638 standard) and tested using a tensile testing machine to record the maximum tensile strength and elongation at break.
[0276] Antibacterial performance test: The samples were cut into 20mm×20mm size and subjected to quantitative contact sterilization test to measure the colony reduction rate.
[0277] Antistatic performance test: The sample was cut into a size of 50 mm × 50 mm, and the surface resistance value was measured using a surface resistance tester.
[0278] Table 1:
[0279]
[0280] Experimental summary:
[0281] By comparing the effects of adding different materials, it was found that nano-silicon dioxide, graphene and carbon nanotubes significantly improved the fire resistance and mechanical strength, antibacterial agents significantly improved the antibacterial properties, and antistatic agents significantly improved the antistatic properties. In particular, nano-silicon dioxide has the most obvious effect on improving fire resistance and mechanical strength, carbon nanotubes have a more prominent effect on improving antistatic properties, and antibacterial agents have the best performance in terms of antibacterial properties.
[0282] Experiment 2: Comparative study on the performance of fire-resistant rubber foam sponge and traditional fire-resistant rubber foam sponge
[0283] Purpose:
[0284] The materials screened out in Experiment 1 (nano-silica, silane coupling agent, antibacterial agent and antistatic agent) were used to prepare fire-resistant rubber foam sponges, and compared with various traditional fire-resistant rubber foam sponges to explore their performance improvements.
[0285] Experimental design:
[0286] Sample preparation:
[0287] Sample A: Traditional fire-resistant rubber foam sponge (control group)
[0288] Sample B: Another traditional fire-resistant rubber foam sponge available on the market
[0289] Sample C: Fireproof rubber foam sponge with nano silicon dioxide (5%), silane coupling agent (2%), antibacterial agent (1%) and antistatic agent (1%) added (the present invention)
[0290] Performance Testing:
[0291] Fire resistance (UL-94 horizontal and vertical burning test)
[0292] Mechanical strength (tensile test)
[0293] Antibacterial properties (quantitative contact bactericidal test)
[0294] Antistatic performance (surface resistance test)
[0295] Experimental steps:
[0296] Sample preparation:
[0297] Sample A and Sample B are commercially available conventional fireproof rubber foam sponges.
[0298] Sample C was prepared according to the optimal material ratio screened out in Experiment 1 and the method of the present invention.
[0299] Performance Testing:
[0300] Fire resistance test: Same as experiment 1.
[0301] Mechanical strength test: Same as experiment 1.
[0302] Antibacterial performance test: Same as experiment 1.
[0303] Antistatic performance test: same as experiment 1.
[0304] Table 2:
[0305]
[0306] Experimental summary:
[0307] The results of this experiment show that the fireproof rubber foam sponge (sample C) with the addition of nano-silica, silane coupling agent, antibacterial agent and antistatic agent is significantly superior to the traditional commercially available fireproof rubber foam sponge (sample A and sample B) in terms of fireproof performance, mechanical strength, antibacterial performance and antistatic performance.
[0308] Fire resistance: The burning time of sample C is 4 seconds without dripping, which is 11 seconds and 8 seconds shorter than that of traditional sample A and sample B, respectively, and there is no dripping.
[0309] Mechanical strength: The maximum tensile strength of sample C is 2.5 MPa, and the elongation at break is 190%, which are significantly better than 1.5 MPa / 150% and 1.7 MPa / 160% of sample A and sample B.
[0310] Antibacterial performance: The colony reduction rate of sample C was 95%, significantly higher than that of sample A and sample B (20% and 25%).
[0311] Antistatic performance: The surface resistance of sample C is 1.0×10 -8 Ω, significantly lower than 1.0×10 -10 Ω and 8.0×10 -9Ω.
[0312] Conclusion: The fireproof rubber foam sponge prepared by the present invention is significantly superior to the traditional fireproof rubber foam sponge in terms of fireproof performance, mechanical strength, antibacterial performance and antistatic performance.
[0313] Experiment 3: Exploring the advantages of the materials and preparation methods of the present invention
[0314] Purpose:
[0315] On the basis of Experiment 2, the advantages of the fire-resistant rubber foam sponge prepared by the material and preparation method of the present invention over the traditional fire-resistant rubber foam sponge are explored.
[0316] Experimental design:
[0317] Sample preparation:
[0318] Sample D: Fire-resistant rubber foam sponge prepared by traditional method (control group 1)
[0319] Sample E: Fire-resistant rubber foam sponge prepared by another conventional method on the market (control group 2)
[0320] Sample F: Fire-resistant rubber foam sponge prepared using the optimal material ratio of Experiment 2 but using the traditional method (Control Group 3)
[0321] Sample G: Fireproof rubber foam sponge prepared by the method of the present invention
[0322] Performance Test:
[0323] Fire resistance (UL-94 horizontal and vertical burning test)
[0324] Mechanical strength (tensile test)
[0325] Antibacterial properties (quantitative contact bactericidal test)
[0326] Antistatic performance (surface resistance test)
[0327] Preparation efficiency (comparison of preparation time and energy consumption)
[0328] Experimental steps:
[0329] Sample preparation:
[0330] Sample D and Sample E are commercially available conventional fireproof rubber foam sponges.
[0331] Sample F was prepared according to the optimal material ratio screened out in Experiment 2 but using the traditional method.
[0332] Sample G was prepared according to the optimal material ratio screened out in Experiment 2 and the method of the present invention.
[0333] Performance Test:
[0334] Fire resistance test: Same as experiment 1.
[0335] Mechanical strength test: Same as experiment 1.
[0336] Antibacterial performance test: Same as experiment 1.
[0337] Antistatic performance test: Same as experiment 1.
[0338] Preparation efficiency test: record the total preparation time and energy consumption of each method and compare the efficiency differences of each sample.
[0339] Table 3:
[0340]
[0341] Experimental summary:
[0342] This experiment compares fire-resistant rubber foam sponges with different preparation methods and material formulas. The results show that:
[0343] Fire performance:
[0344] The burning times of samples D and E (prepared by conventional methods) were 10 seconds and 12 seconds respectively, and both had dripping.
[0345] Sample F (optimal material ratio but prepared by conventional method) had a burn time of 6 seconds with no dripping.
[0346] The burning time of sample G (prepared by the method of the present invention) was 4 seconds, with no dripping, which was significantly better than the other samples.
[0347] Mechanical strength:
[0348] The maximum tensile strengths of Sample D and Sample E are 1.8 MPa and 1.7 MPa, respectively, and the elongations at break are 160% and 150%, respectively.
[0349] The maximum tensile strength of sample F is 2.2 MPa, and the elongation at break is 180%.
[0350] Sample G has the best performance with a maximum tensile strength of 2.5 MPa and an elongation at break of 190%.
[0351] Antimicrobial Properties:
[0352] The colony reduction rates of sample D and sample E were 30% and 25%, respectively.
[0353] The colony reduction rate of sample F was 70%.
[0354] The colony reduction rate of sample G was 95%, which was significantly higher than that of other samples.
[0355] Antistatic properties:
[0356] The surface resistances of sample D and sample E are 1.0×10^9Ω and 8.0×10^9Ω, respectively.
[0357] The surface resistance of sample F is 5.0×10^8Ω.
[0358] The surface resistance of sample G is 1.0×10^8Ω, which performs best.
[0359] Preparation efficiency:
[0360] The preparation time of sample D and sample E is 8 hours and 9 hours respectively, and the energy consumption is 100 kWh and 110 kWh respectively.
[0361] The preparation time of sample F is 8 hours and the energy consumption is 100 kWh.
[0362] The preparation time of sample G is 6 hours and the energy consumption is 80kWh, which is significantly better than other samples.
[0363] Conclusion: The fireproof rubber foam sponge (sample G) prepared by the method of the present invention is significantly superior to the samples prepared by the traditional method in terms of fireproof performance, mechanical strength, antibacterial performance and antistatic performance, and has higher preparation efficiency and lower energy consumption. In particular, compared with sample F prepared by the traditional method using the same material formula, the method of the present invention shows significant advantages in preparation efficiency and final performance, demonstrating the significant superiority and practical value of the method of the present invention.
[0364] Experiment 4: Exploring the advantages of the material and preparation method of the present invention in terms of weather resistance and cost-effectiveness
[0365] Purpose:
[0366] Based on the above experiments, the advantages of the fire-resistant rubber foam sponge prepared by the material and preparation method of the present invention in terms of weather resistance and cost-effectiveness are further explored.
[0367] Experimental design:
[0368] Sample preparation:
[0369] Sample H: Fire-resistant rubber foam sponge prepared by traditional method (control group 1)
[0370] Sample I: Fire-resistant rubber foam sponge prepared by another conventional method on the market (control group 2)
[0371] Sample J: Fire-resistant rubber foam sponge prepared using the optimal material ratio of Experiment 2 but using traditional methods (Control Group 3)
[0372] Sample K: Fireproof rubber foam sponge prepared by the method of the present invention
[0373] Performance Test:
[0374] Weather resistance (humidity and heat aging test, freeze-thaw cycle test)
[0375] Cost-effectiveness (production cost analysis, service life assessment)
[0376] Experimental steps:
[0377] Sample preparation:
[0378] Sample H and Sample I are commercially available conventional fireproof rubber foam sponges.
[0379] Sample J was prepared according to the optimal material ratio screened out in Experiment 2 but using the traditional method.
[0380] Sample K was prepared according to the optimal material ratio screened out in Experiment 2 and the method of the present invention.
[0381] Weathering test:
[0382] Damp heat aging test: Each sample was placed in an environment of 85°C and 85% relative humidity, and the change in mechanical strength of the sample was measured every 30 days for 6 months.
[0383] Freeze-thaw cycle test: Each sample was subjected to freeze-thaw cycles (-20°C to +20°C), and the change in mechanical strength of the sample was measured every 30 days for 6 months.
[0384] Cost-effectiveness test:
[0385] Production cost analysis: Analyze the production cost of each sample, including raw material cost, energy consumption, and production time.
[0386] Service life evaluation: Based on the aforementioned weather resistance test data, the expected service life of each sample was evaluated.
[0387] Table 4:
[0388]
[0389] Experimental summary:
[0390] This experiment compares fire-resistant rubber foam sponges with different preparation methods and material formulas. The results show that:
[0391] Weather resistance:
[0392] The changes in the wet heat aging strength of sample H and sample I (prepared by the traditional method) were -20% and -18%, respectively, and the changes in the freeze-thaw cycle strength were -25% and -23%, respectively.
[0393] Sample J (optimal material ratio but prepared by conventional method) showed a strength change of -10% for wet heat aging and -15% for freeze-thaw cycle strength.
[0394] The wet heat aging strength change of sample K (prepared by the method of the present invention) is -5%, and the freeze-thaw cycle strength change is -10%, which is significantly better than other samples.
[0395] Cost-effectiveness:
[0396] The production costs of sample H and sample I are 100 yuan / m2 and 110 yuan / m2 respectively.
[0397] The production cost of sample J is 120 yuan / square meter.
[0398] The production cost of sample K is 90 yuan / square meter, which is significantly lower than other samples.
[0399] The expected service life of Sample H and Sample I is 10 years and 12 years, respectively.
[0400] The expected service life of sample J is 15 years.
[0401] The expected service life of sample K is 20 years, which is significantly higher than that of other samples.
[0402] Conclusion: The fireproof rubber foam sponge (sample K) prepared by the method of the present invention is significantly superior to the sample prepared by the traditional method in terms of weather resistance and cost-effectiveness. Specifically, it is manifested in smaller changes in strength after hygrothermal aging and freeze-thaw cycles, lower production costs and longer expected service life. These advantages further demonstrate the significant superiority and wide application potential of the method of the present invention.
[0403] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. Fireproof rubber foam sponge, characterized in that: Calculated by weight percentage, the invention comprises the following components: 50%-60% polyether polyol, 30%-40% isocyanate, 2%-5% water, 0.3%-1% catalyst, 0.5%-2% foam stabilizer, 5%-10% flame retardant, 3%-6% nano-silicon dioxide, 8%-15% bio-based polyol, 0.5%-2% antibacterial agent, 1%-3% antistatic agent and 1%-3% silane coupling agent.
2. The fireproof rubber foam sponge according to claim 1, characterized in that: The catalyst is optionally selected from one of an organic tin compound, a tertiary amine catalyst or an organic metal compound, and the foam stabilizer is optionally selected from one of a siloxane stabilizer, a polyether stabilizer or an organic silicon polyether copolymer.
3. The fireproof rubber foam sponge according to claim 1, characterized in that: The flame retardant is optionally selected from one of halogen flame retardants, phosphorus flame retardants or nitrogen flame retardants, and the antibacterial agent is optionally selected from one of silver nanoparticles, copper nanoparticles or triclosan.
4. The fireproof rubber foam sponge according to claim 1, characterized in that: The antistatic agent is optionally selected from alkyl dimethyl benzyl ammonium chloride, tributyl phosphate or acetylene black, and the silane coupling agent is optionally selected from γ-aminopropyl triethoxysilane, γ-glycidyl ether oxypropyl trimethoxysilane or vinyl trimethoxysilane.
5. A method for preparing a fireproof rubber foam sponge, characterized in that: The method is prepared by using the fireproof rubber foam sponge component material according to any one of claims 1 to 4, comprising the following steps: S1, mixing nano-silica with a silane coupling agent and treating it by aerosol-assisted assembly technology; S2, dissolving polyether polyol, bio-based polyol and water in a suitable solvent, and stirring with a magnetic stirrer for 25-30 minutes; S3, add foam stabilizer, catalyst and pretreated nano-silicon dioxide solution, and continue stirring for 10-15 minutes; S4, subjecting the uniformly mixed polyol mixture and isocyanate to cold plasma treatment in a low temperature environment; S5. Perform initial curing at room temperature; S6, performing secondary curing; S7, impregnating the solidified sponge with an antibacterial agent and an antistatic agent; S8. Drying is performed in a vacuum dryer.
6. The method for preparing a fireproof rubber foam sponge according to claim 5, characterized in that: The aerosol-assisted assembly technology process in step S1 specifically includes the following steps: Solution atomization: Use an ultrasonic atomizer to atomize the uniformly dispersed nano-solution into tiny droplets. The frequency of the ultrasonic atomizer is set between 1.7MHz-2.4MHz to produce droplets with a diameter of about 1-10 microns; Aerosol formation: The atomized droplets are transported to the aerosol reactor through the carrier gas to form a stable aerosol; Aerosol reaction: In the aerosol reactor, the electric field and airflow are used to control the dispersion and deposition of droplets. The electric field strength is set at 0.5-2kV / cm, and the airflow velocity is set at 0.1-1m / s. The nanomaterials are evenly dispersed and covered on the substrate or other target surface in the reactor; Deposition and drying: At room temperature, the aerosol passing through the aerosol reactor is uniformly deposited under the action of the electric field and airflow. The deposition time is 10-30 minutes to form a uniform nano-coating. The deposited material is dried at 60℃-80℃ for 30-60 minutes, leaving uniformly distributed nanoparticles.
7. The method for preparing a fireproof rubber foam sponge according to claim 6, characterized in that: The carrier gas is nitrogen or air, and its flow rate is set at 1-5 L / min.
8. The method for preparing a fireproof rubber foam sponge according to claim 5, characterized in that: The appropriate solvent in step S2 is alcohol or acetone, the curing time in step S5 is 1-3 hours, the curing temperature in step S6 is 70-90° C., and the secondary curing time is 1-4 hours.
9. The method for preparing a fireproof rubber foam sponge according to claim 5, characterized in that: The immersion treatment in step S7 specifically includes the following steps: The solidified sponge is completely immersed in the comprehensive functional solution, and the surface and the inside of the sponge are fully in contact with the solution; In an environment of 20℃-30℃, gently stir or shake the solution and soak for 20-40 minutes; Remove the sponge: Once the dipping is complete, remove the sponge from the solution and gently squeeze to remove any excess solution.
10. The method for preparing a fireproof rubber foam sponge according to claim 9, characterized in that: The comprehensive functional solution is formed by mixing an antibacterial agent solution and an antistatic agent solution in a ratio of 1:1.